Gendered and caste tragedies in the coir industries: Evidence from Kerala - P, Linshi.; Manimekalai, N. (Edelweiss Applied Science and Technology, 2025)
This study examines the historical evolution of women’s participation in Kerala’s coir industry, focusing on their role in the spinning sector and the socio-economic contexts shaping their engagement. The research relies on secondary data collected from government reports and previous scholarly studies. A historical and comparative approach was used to analyze women’s labor participation across the 1980s, 1990s, 2000s, 2010s, and 2020s. The analysis shows that women remain a significant part of the coir workforce despite persistent challenges such as low wages, gender-based discrimination, and limited opportunities for advancement. Globalization, technological changes, and government policies have significantly influenced their employment patterns, leading to both opportunities and constraints. Women’s continued participation in coir production reflects resilience and underscores their struggle for economic empowerment, social recognition, and gender equality. The findings highlight the need for policy interventions to ensure fair wages, strengthen social protection, and promote inclusive development for women in traditional industries.